A produção associada do povo Puruborá, aldeia Aperoi – RO : "trabalho de ganhar", "trabalho de viver", educação, saberes e resistência - Ramos, Anatália Daiane de Oliveira (2019)
This thesis is a synthesis of a scientific research carried out in Aperoi village, located in the municipality of Seringueiras, State of Rondônia, with the Puruborá indigenous people. It is linked to the Study and Research Group on Labor and Education (GEPTE) of the research line “Social movements, politics and popular education” of the Postgraduate Program in Education (PPGE) of the Institute of Education (IE) of the Federal University of Mato Grosso (UFMT). The research aimed to investigate the production of material and immaterial life of the Puruborá people of Aperoi village in Seringueiras, Rondônia and the “rescued”, constructed and “transmitted” knowledge, during this production. The Purubora people are an indigenous people of the state of Rondônia, who were contacted by Marechal Cândido Mariano da Silva Rondon in 1909. In the 1990s, these people were denied their ethnic identity by the National Indian Foundation (Funai) and were expelled from their traditional territory. In the 2000s, the Puruborá people “reemerged”, beginning a process of struggle in favor of the recognition of their indigenous identity, the revitalization of their traditional culture, the (re)demarcation of their territory and the realization of other indigenous rights. It was a qualitative research based on the theoretical-methodological framework of dialectical historical materialism and that used some elements of the participant research. The research instruments used were documentary analysis, semi-structured interviews, workshops and participant observation carried out in the village Aperoi and recorded through a field diary, photographs and videos. There were ten semi-structured interviews with Puruborá over 18 years old and two workshops with the people of the community. The analysis took place through the triangulation of the data, articulating them with the theoretical contribution and the research objectives. In Aperoi village there is the “work of earning” and the “work of living”, which have educational dimensions. It was concluded that the material and immaterial production of the Puruborá people of Aperoi village in Seringueiras-RO is achieved through the Associated Production of life, through the mobilization, retaking, sharing and historical and daily reconstruction of a series of knowledge, be they traditional – related to traditional territory, Purubora language, traditional painting, the use of medicinal plants, festivals, solidarity, commensality, reciprocity, etc. – be built after contact with Marechal Rondon.